(untitled) (Research, Society and Development, 2021)
The aim of this study is to investigate the use of biosafety practices by health professionals working in an ICU of a public hospital in Teresina-PI. This is a cross-sectional study, approved by the ethics committee (2,583,723), conducted at a state hospital in Teresina-PI, using questionnaires to ICU health professionals. The data were analyzed using the SPSS 17.0 and BioEstat 5.0 programs, using the Chi-square, Wilcoxon and Kruskal Wallis tests. Values with p <0.05 were considered significant. 26 professionals were interviewed, with a predominance of those with more than 10 years of training (53.8%, p <0.006, n = 14), with more than 3 years of professional experience (76.9%, n=20, p=0.001***) and older than 3 years working at the referred hospital (76.9%, n = 20, p <0.001***). 96.2% reported using PPE, with use restrictions for propes (92.3%) and goggles (84.6%). 18 (69.2%) reported that they were charged with the knowledge of biosafety standards by the hospital, differing with the perception of knowledge and updating of them. There is a deficiency in the knowledge of professionals in the knowledge and rigor of biosafety practices.